Therapeutic application of Achillea millefolium L. in female reproductive diseases from the viewpoint of Persian medicine and current medicine - Somayeh Zakeri; Narjes Gorji; Reihaneh Moeini; zahra Memariani (Institue of Medicinal Plants, ACECR, 2019)
Introduction: In Persian medicine (PM), Achillea millefolium L. has a wide range of applications in the treatment of several diseases. The aim of this study is to introduce the viewpoints of PM scholars about this herb in the field of female diseases and to compare them with the recent studies. Methods: In this review study, therapeutic applications of Achillea millefolium in the field of female diseases were collected from credible Persian medical sources from 4th to 14th lunar centuries then current scientific databases such as PubMed and Google scholar were searched by using key world Achillea millefolium for collecting the findings of clinical, experimental and in vitro studies about this herb in the field of obstetrics and gynecology to compared to the PM scholarschr('39') viewpoints. Results: in PM, Achillea millefolium is recommended for treatment various female reproductive diseases such as menstrual disorders, facilitating labor, reducing adhesions of cervix, controlling uterine infections. In recent studies, therapeutic effects of this herb on ovarian cyst, menstrual cycle regulation and dysmenorrhea have been reported. Also, in several studies, the antibacterial and antifungal effects of this plant on controlling infections have been investigated; as well the extract of this plant has been effective in inhibiting the proliferation of ovarian adenocarcinoma cells. Conclusion: Considering the extensive uses of Achillea millefolium reflected in PM and recent studies, it seems that this plant can be used in many fields of female diseases to provide ideas for research and therapy